A PRELIMINARY SURVEY OF THE FISH AND FISHERIES OF A FIVE-MILE STRETCH OF THE HOOGHLY RIVER NEAR BARRACKPORE - David, A (Indian Journal of Fisheries, 2016)
A FISHERIES survey of the Hooghly river adjoining Barrackpore area wassuggested to the author by Dr. T. J. Job. This survey was felt to be ofspecial significance since the adjoining stretch of the river represents a transitionalstage between the typically estuarine conditions lower down and thepurely freshwater stretch above